A test of the Janzen‐Connell hypothesis in a species‐rich Mediterranean woodland. Issue 11 (12th November 2021) - Teste, François P.; Laliberté, Etienne
Abstract: The Janzen‐Connell (JC) hypothesis predicts that conspecific negative density dependence contributes to the maintenance of plant diversity by lowering the recruitment of locally abundant plant species. The JC hypothesis is a widely evoked explanation for the high species diversity in tropical forests, but remains poorly tested in other species‐rich systems such as Mediterranean woodlands. As such, we tested if the JC operates and the role of soil‐borne oomycetes in a species‐rich Mediterranean woodland of Western Australia, where post‐fire recruitment can lead to high seedling densities, using the common Banksia attenuata as a case study. We attempted to decipher the effects of oomycete pathogens and distance from conspecific trees on intraspecific seedling survival and growth. Contrary to the JC hypothesis, we found little evidence of negative density dependence, but our results suggest positive density dependence survival under conspecific trees. Oomycete‐driven mortality in seedlings was also found regardless of the type of tree. Our results suggest that short‐term seedling recruitment patterns in this species‐rich, fire‐prone ecosystem do not follow the JC hypothesis. Future studies should explore whether negative conspecific density and distance dependence could play a greater role in later stages of the post‐fire recovery process.